2020
DOI: 10.1111/ejn.15077
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the orexin/hypocretin system is not limited to narcolepsy but has far‐reaching implications for neurological disorders

Abstract: contributed equally to this work. Claudio Liguori served as consultant for EISAI and MSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 182 publications
(216 reference statements)
0
12
0
Order By: Relevance
“…Alternatively, a sex difference in CSF OXA could be unique for nocturnal laboratory rats. Studies involving humans have mostly found similar CSF orexin in males and females (see Berteotti et al., 2020), but some of these studies had few healthy controls and may have been statistically underpowered to detect a sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, a sex difference in CSF OXA could be unique for nocturnal laboratory rats. Studies involving humans have mostly found similar CSF orexin in males and females (see Berteotti et al., 2020), but some of these studies had few healthy controls and may have been statistically underpowered to detect a sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, slow metabolic state signalling to orexin neurons via nutrients and hormones (2224) would place orexin as a centrepiece in mediating these transitions during, for example, foraging behaviours. The implications of the present results may also be useful for diagnosing orexin cell loss, which occurs in human narcolepsy and is currently diagnosed through highly invasive procedures (25), as well as give insight into other neurological disorders (26).…”
mentioning
confidence: 88%
“…Fronczek et al [ 152 ] quantified hypocretin neurons and measured hypocretin levels in the cerebrospinal fluid (CSF) of post-mortem hypothalamus of AD patients and found a 40% decrease in hypocretin neurons and a 14% decrease in CSF hypocretin-1 levels. Increased CSF-hypocretin levels, on the other hand, have been reported in some Alzheimer’s disease patients [ 153 , 154 , 155 , 156 , 157 , 158 ]. As low hypocretin decreases amyloid release, NT1 patients who have lost most of their hypocretin-containing neurons, seem to have a lower risk of developing AD [ 40 , 41 ].…”
Section: Pathophysiology and Links With Other Diseasesmentioning
confidence: 99%